Prevalence of Osteoporosis and Osteoporotic Vertebral Fractures in Turkish Patients with Ankylosing Spondylitis: A Retrospective Cross-sectional Study - Ece Çınar; Yeşim Kirazlı; Duygu Kerim; Gonca Karabulut (Galenos Yayinevi, 2023)
Objective: Ankylosing spondylitis (AS) is a chronic inflammatory disease mainly affecting the vertebral column that is the prototype of the spondyloarthritides and is characterized by bone marrow edema, osteitis, erosions, enthesopathy, new bone formations and sclerosis. A decrease in bone mineral density (BMD), in addition to later restrictions in movement and muscle weakness, predisposes the patient to osteoporotic fractures. In this retrospective study, we aimed to assess the prevalence of osteoporosis (OP) and osteoporotic vertebral fractures. Materials and Methods: This study was conducted in Ege University Faculty of Medicine, Departments of Physical Medicine and Rehabilitation and Rheumatology on patients who were diagnosed with AS and who had in the previous year received a BMD examination. Demographic and disease information, Bath Ankylosing Spondylitis Disease Activity index scores and if present, findings of vertebral radiographs and vitamin D levels were recorded from patient files. These parameters were used to compare patients with or without OP. Results: One hundred consecutive patients that were seen in our outpatient clinic and who met the inclusion criteria were enrolled in this study. In BMD examinations, 48% of subjects were found to have OP or osteopenia. Sixty radiographs were reached and 16% of subjects were found to have at least one vertebral fracture. We detected a significant difference between these groups regarding age, sex, disease duration and BMD and T-scores at the levels of femur neck and total hip (p<0.05). We did not detect a significant correlation between clinical parameters and parameters related to OP (p>0.05). Conclusion: The presence of concomitant OP in patients with AS is significant for increased fracture risk, also recurrent vertebral fractures may exacerbate the spinal deformities caused by the disease itself. It bears importance that clinicians be aware of increased risk of OP to be able to better manage pain and function loss in this patient population.